Seasonal change of multifrequency backscatter in three Baltic Sea habitats - Schulze, Inken; Gogina, Mayya; Schönke, Mischa; Zettler, Michael L.; Feldens , Peter (Frontiers in Remote Sensing, 2022)
This study investigates the seasonality of acoustic backscatter intensities, exploring three habitats in the southwestern Baltic Sea: (1) a mussel covered reef, (2) coarse sand and gravel and (3) seagrass meadows. Backscatter information of different, partly calibrated, frequencies (200, 400, 550 and 700 kHz) were collected in three seasons (May, August, October). The acoustic data were supported by point-samples and video profiles for grain size and benthic community analysis. Angular response curves helped to quantify the seasonal backscatter response of the different frequencies. The multifrequency and multiseasonal backscatter maps distinguish the three habitats and reveal variable seasonal differences in acoustic backscatter, but not all changes in benthic community can be recognized in the acoustic data. (1) The high backscatter response of the mussel-covered reef shows little seasonal differences and was frequency independent. (2) The ecologically valuable coarse sand and gravel areas show small-scale seasonal alterations in the sediment composition and morphology, mainly caused by changes in local hydrodynamics. Higher frequencies were found best suited to identify coarse sand and gravel. (3) Seagrass meadows seasonality is dominated by growth of seagrass blades, increasing the backscatter response compared to bare sand. The use of multiple frequencies is beneficial as the low frequency is sensitive to changes in the shallow subsurface and benthic features such as seagrass rhizomes, while the higher frequency highlight changes related to coarser sediment.